(untitled) (Research, Society and Development, 2021)
Background: Natal teeth are defined as teeth present at birth, while neonatal dental elements are those that hatch within 30 days after this event, and these changes from normality are more frequent in babies with cleft lip and palate. Conservative treatment consists of follow-up in cases where there is no harm to the mother and child. However, the presence of these elements can cause discomfort during suction, laceration of the mother’s breasts and aspiration of teeth, requiring surgical removal. Objective and case report: the aim of this work is to present two cases of natal and neonatal teeth in babies with cleft lip and palate. The first case is intended to report a neonatal tooth in the anterior region of the mandible. The second, in sequence, reports the presence of a natal tooth in the maxillary region, both of which are deciduous dentition. The treatment of choice for the two cases mentioned above involved the removal of the elements and subsequent follow-up, a therapy chosen due to suction difficulties, mobility that can predispose to accidental aspiration of the element by the baby, injuries to the breast during breastfeeding and damage to molding in cases where there is a need to make intraoral plates to help with feeding. Conclusion: Although conservative treatment is a viable option in some cases of natal and neonatal teeth in patients with cleft lip and palate, surgical removal is an effective therapy in cases where the dental element causes significant damage to the mother and baby.